PEMBINAAN IBADAH SHALAT BAGI ANAK USIA DINI PADA MASA NEW NORMAL DI JORONG ARO, KECAMATAN GUNUNG TALANG, KABUPATEN SOLOK - Jumita Permata Sari; Charles Charles; Salmi Wati; Iswantir M (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the prohibition to carry out learning activities at the TPA during the new normal, causing parents to only be able to foster children's prayer at home, even though not all parents have the understanding in teaching prayer to children as children get when studying at home. TPA, so that in the process the parents experienced several problems. Like some parents are not firm when ordering their children to pray so that children underestimate it, children also do not have knowledge about the terms and pillars of prayer even though at this age the child must be taught about this before he is ordered to pray. This research is a type of field research, which is a research that is carried out systematically by picking up existing data in the field, explaining and describing the situation and phenomena more clearly regarding the situation that occurs, using a qualitative approach. The results showed that the methods parents used were the habit method, the exemplary method, the advice method and the punishment method. The average development of reading/prayer movement movements has not worked well, where children only know the prayer movements but there are still many improvements to the prayer readings.. The obstacle faced when coaching prayer worship is that children sometimes feel lazy and tend to like playing games on their cellphones until forgetting time, lack of understanding of parents in teaching children about praying at home, busy parents working during the day so they can't monitor their children.